Dietary Supplementation with Encapsulated or Non-Encapsulated Sodium Butyrate Enhances Growth, Antioxidant Defense, Immunity, and Gut Health in Largemouth Bass (Micropterus salmoides) - Minghui He; Zhiwei Zou; Wanjia Zhu; Haipeng Li; Ting Liang; Liwei Liu; Jianmei Su (Microorganisms)
This study aimed to evaluate the effects of dietary supplementation with sodium butyrate (SB) in different forms on the growth performance, antioxidant capacity, immune response, and intestinal health of largemouth bass (Micropterus salmoides). Five diets were formulated: a basal diet (SB0), diets with 1000 (ESB1), 1500 (ESB2), and 2000 mg/kg encapsulated SB (ESB3), and a diet with 2000 mg/kg raw powder sodium butyrate (RSB, non-encapsulated). After 49 days of feeding trials, the ESB2 group exhibited significantly higher weight gain and specific growth rates and a lower feed coefficient than those of the SB0 group (p < 0.05). Compared with the SB0 group, proximal intestinal villus length and width were significantly increased in the ESB1, ESB2, and ESB3 groups (p < 0.05). The expressions of tight junction genes zo-1, claudin-1, and claudin-4 were up-regulated in these SB-supplemented groups and most pronounced in the ESB2 group (p < 0.05). Compared with the SB0 group, antioxidant enzyme activities (catalase and superoxide dismutase) and their gene expressions increased in the ESB1, ESB2, and RSB groups (p < 0.05). Immune-related genes il-10 and tgf-β1 were up-regulated in the ESB1 and ESB2 groups, while their il-8, il-1β, and tnf-α were down-regulated (p < 0.05). The ESB2 group had higher intestinal abundance of Firmicutes and Lactobacillus. In conclusion, dietary supplementation with 1500 mg/kg encapsulated SB (ESB2) improved growth, antioxidant capacity, immunity, and gut health in largemouth bass.